Monopolistic pricing with goal-driven consumers - Giorgos N. Diakoulakis (ZBW - Leibniz Information Centre for Economics, 2024)
In this article, we theoretically explore monopolistic pricing when a (representative) consumer exhibits multiple goals.
Keywords: D42; D90; D21; 330; monopolistic firm; personalized pricing; goal-driven consumers